Viabilidade energética da biomassa da palma forrageira no Semiárido - Cavalcanti, Maria Luíza Coelho (2020)
The semi-arid region consists of an area with 1,128,697 km², equivalent to 11% of the national territory. The caatinga is the endemic biome of this region and occupies an area of 844,453 km², which extends over the domain of semiarid climates and constitutes a unique biological heritage, where several species of palma are found and which can be found throughout paraíba state. This work was developed in partnership with the experimental station of the national institute of the semi-arid (insa) and the multi-user laboratory of animal nutrition of the federal university of rio grande do norte (ufrn), in order to analyze the energy potential of the biomass of the forage palm miúda / doce (nopalea cochenillifera) and baiana / palmepa (nopalea cochenillifera salm - dyck) species. Through this analysis it was possible to verify that it is of great use not only for the production of human food and fodder for animals in extreme periods of drought in the semi-arid region of paraíba, but also very viable and promising as an energy source with possibilities of application in briquette production (solid fuel) as well as bioethanol production (liquid fuel) due to its characteristics, as well as the content of carbohydrates, hemicellulose and lignin concentrated in the two studied species. Therefore, being found in palma miúda, total carbohydrates (87.42%), hemicellulose (22.60%) and lignin (0.78%) and in palma baiana, total carbohydrates (83.84%), hemicellulose (11 , 17%) and lignin (0.13%). In addition, a field study was carried out in which the entire planting process of these palms was monitored, using geotechnologies to perform a georeferencing of the subdivided plot of the planted area, in order to understand the cultivation of the forage palm as well as to measure its production bias and economic value that serves as a technological lever in the production of biofuels, in the socioeconomic development of the region, in addition to collaborating with mitigating actions in favor of the reforestation of desertified areas in the semiarid region.